ПОЛІТИКА НІМЕЦЬКО-РУМУНСЬКОЇ ВЛАДИ У СФЕРІ ОСВІТИ НА ОКУПОВАНІЙ ТЕРИТОРІЇ ПІВДНЯ УКРАЇНИ (Zaporizhzhia Historical Review, 2021)
The article is devoted to the educational institutions’ development for the occupied population of the South of Ukraine during the German-Romanian authority. The author considers educational system folksdoiche (Volks Deutsche) for ethnic Germans, which had common traits with German educational system.